Study of Seed Germination by Soaking Methode of Cacao (Theobroma cacao L.) - Sulistyani Pancaningtyas; Teguh Iman Santoso; Sudarsianto . (Indonesian Coffee and Cocoa Research Institute, 2014)
Study of germination methods conduct to get information about seed viability based on germination rate, percentage of germination and vigority. Germination methods was studied to get the efficiency and effectivity of germination, easy to handle, low costs with high vigority. Sand and gunny sack methods for germination, need extensive place and 3-4 days germination period after planting. This research will study the alternative of germination method with soaking. This method can be accelerating germination rate and effectively place usage without decreasing the quality of cacao seedling.The research was done at Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institue. This research consist of two experiment was arranged based on factorial completely random design. First experiment will observed to compared germination rate and the second experiment will observed seedling quality between soaking and wet gunny sack germination method.The results showed that length of radicel on soaking method longer than wet gunny sack method. Growth of radicel started from 2 hours after soaking, moreover length of radicel at 4 hours after soaking have significant different value with gunny sack method. On 24 hours after soaking have 3,69 mm and 0,681 mm on wet gunny sack treatment. Except lengt of hipocotyl, there is not different condition between seedling that out came from soaking and wet gunny sack method. Length of hipocotyl on 36 hours after soaking have 9,15 cm and significant different between wet gunny sack germination method that have 5,40 cm. Keywords : seed germination, soaking method, Theobroma cacao L., cocoa seedlings